2014
DOI: 10.3164/jcbn.13-100
|View full text |Cite
|
Sign up to set email alerts
|

Maternal protein restriction induces alterations in hepatic tumor necrosis factor-α/CYP7A1 signaling and disorders regulation of cholesterol metabolism in the adult rat offspring

Abstract: It is well recognized that adverse events in utero impair fetal development and lead to the development of obesity and metabolic syndrome in adulthood. To investigate the mechanisms linking impaired fetal growth to increased cholesterol, an important clinical risk factor characterizing the metabolic syndrome and cardiovascular disease, we examined the impact of maternal undernutrition on tumor necrosis factor-α (TNF-α)/c-jun N-terminal kinase (JNK) signaling pathway and the cholesterol 7α-hydroxylase (CYP7A1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 51 publications
6
34
0
Order By: Relevance
“…For example, serum TCH concentrations are increased in offspring rats with PEE [21]. Similarly, serum TCH concentrations in prenatal food-restricted offspring are also increased, and even hepatic cholesterol accumulation has been found [10, 29]. Some epidemiological investigations have found that the incidence of serum cholesterol disorder is increased in 20-year-old adults with low birth weight and is accompanied by increased serum LDL-C and decreased HDL-C levels [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, serum TCH concentrations are increased in offspring rats with PEE [21]. Similarly, serum TCH concentrations in prenatal food-restricted offspring are also increased, and even hepatic cholesterol accumulation has been found [10, 29]. Some epidemiological investigations have found that the incidence of serum cholesterol disorder is increased in 20-year-old adults with low birth weight and is accompanied by increased serum LDL-C and decreased HDL-C levels [30].…”
Section: Discussionmentioning
confidence: 99%
“…Because the liver is the largest cholesterol metabolic organ, hepatic cholesterol metabolic disorders can directly cause blood cholesterol disorders and are involved in many types of cerebrovascular diseases. It has been reported that increased blood cholesterol level that both occurs after the birth of offspring, and is caused by an adverse prenatal environment may be related to the changes in hepatic cholesterol metabolism [10, 13, 14]. Therefore, the changes in hepatic cholesterol metabolism in IUGR offspring are worthy of great attention [10, 15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrauterine growth retardation (IUGR) is defined as a developing baby weighing either 10% of or 2 SD less than the mean body weight of other babies of the same gestational age (5). In recent years, population studies and animal experiments have found that children with IUGR have elevated blood cholesterol levels and are susceptible to metabolic diseases in adulthood (6)(7)(8). These results suggest that hypercholesterolemia and its associated diseases may have intrauterine developmental origins.…”
mentioning
confidence: 99%
“…Intrauterine programming refers to a scenario in which an intrauterine fetus is exposed to an adverse environment, leading to fetal organ development and functional changes; these changes can persist after birth (13,14). It has been suggested that the elevation of blood cholesterol levels in the IUGR due to the adverse environment during pregnancy may be related to changes in the expression of cholesterol-related genes in the livers of offspring (6,15). However, an intrauterine programming mechanism for PCE-induced hypercholesterolemia in offspring has not been reported.…”
mentioning
confidence: 99%